THE REPRESENTATION OF ORIENTALISM NEGOTIATION IN ROWELL'S ELEANOR AND PARK - Berlian Ayu Pangestu; Supiastutik Supiastutik; L. Dyah Purwita Wardani SWW (UIN Raden Mas Said Surakarta, 2023)
This paper explores the representation of orientalism negotiation in a novel entitled Eleanor and Park, written by Rainbow Rowell. This study utilized a descriptive-qualitative method to analyze the story by applying the representation theory proposed by Stuart Hall, especially the constructive approach suggested by Foucault. It focuses on the construction of meaning through language related to the depiction of oriental characters and how they struggle and respond to the treatments they receive from white people. Operating the concepts of orientalism from Edward Said and the discursive approach proposed by Foucault, this study explores the ideological position of the writer as well. From this study, it is found that as an American white writer, Rowell shows the negotiation of the orientalism concept. Presenting the white characters with oriental characteristics and non-white characters with accidental qualities, Rowell exemplifies the strategic way to create racial harmony. However, the efforts to create characterizations as forms of negotiation against orientalism have reached a dead end because the readers are more impressed by the honored class, which consists of mostly white students, who are able to subvert the negotiations on orientalism made by the author.